2021
DOI: 10.3390/genes12101506
|View full text |Cite
|
Sign up to set email alerts
|

GWAS Meta-Analysis Reveals Shared Genes and Biological Pathways between Major Depressive Disorder and Insomnia

Abstract: Major depressive disorder (MDD) is one of the most prevalent and disabling mental disorders worldwide. Among the symptoms of MDD, sleep disturbance such as insomnia is prominent, and the first reason patients may seek professional help. However, the underlying pathophysiology of this comorbidity is still elusive. Recently, genome-wide association studies (GWAS) have begun to unveil the genetic background of several psychiatric disorders, including MDD and insomnia. Identifying the shared genomic risk loci betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…For example, Santiago et al reported that changes in cortisol are the modulator between sleep disturbances and depression ( 6 ). Lin et al found 719 shared genes between MD and insomnia, which provide insight into the genetic substrates in depression individuals' comorbid insomnia symptoms ( 7 ). Yan et al proposed that dysfunctional glymphatic pathway may serve as a bridge between sleep disturbance and depression ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Santiago et al reported that changes in cortisol are the modulator between sleep disturbances and depression ( 6 ). Lin et al found 719 shared genes between MD and insomnia, which provide insight into the genetic substrates in depression individuals' comorbid insomnia symptoms ( 7 ). Yan et al proposed that dysfunctional glymphatic pathway may serve as a bridge between sleep disturbance and depression ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The next strongest signal observed on Butyrophilin (BTN) family genes was another common finding in the genome-wide cross-trait meta-analysis of DCC and MDD (index SNP rs67777156, P meta = 2.20 × 10 −15 ). Among its related pathways are Butyrophilin (BTN) family interactions and Class I MHC-mediated antigen processing and presentation ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reactome enrichment of HATs acetylate histones, HDACs deacetylate histones, HDMs demethylate histones, DNA methylation, and developmental biology together suggested the effects of both genetic and epigenetics on DCC/MDD and DCC/neuroticism. A study has revealed the shared pathway including DNA methylation between MDD and Insomnia ( 20 ). Inhibition of DNA methyltransferase 3a by polyphenol from coffee was also confirmed ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations